2015
DOI: 10.1093/mnras/stv1329
|View full text |Cite
|
Sign up to set email alerts
|

The triggering of local AGN and their role in regulating star formation

Abstract: We explore the processes that trigger local AGN and the role of these AGN in regulating star formation, using ∼550 nearby galaxies observed by the mJy Imaging VLBA Exploration at 20 cm (mJIVE) survey. The 10 7 K brightness temperature required for an mJIVE detection cannot be achieved via star formation alone, allowing us to unambiguously detect nearby radio AGN and study their role in galaxy evolution. Radio AGN are an order of magnitude more common in early-type galaxies (ETGs) than in their late-type counte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 109 publications
5
35
0
Order By: Relevance
“…Our results appear consistent with recent work that has suggested a strong connection between merging and the onset of AGN activity at low redshift (e.g. Koss et al 2010;Ellison et al 2011;Scott & Kaviraj 2014;Kaviraj et al 2015), although the role of mergers in triggering AGN may become negligible at high redshift (e.g. Chiaberge & Marconi 2011;Kocevski et al 2012;Schawinski et al 2012).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Our results appear consistent with recent work that has suggested a strong connection between merging and the onset of AGN activity at low redshift (e.g. Koss et al 2010;Ellison et al 2011;Scott & Kaviraj 2014;Kaviraj et al 2015), although the role of mergers in triggering AGN may become negligible at high redshift (e.g. Chiaberge & Marconi 2011;Kocevski et al 2012;Schawinski et al 2012).…”
supporting
confidence: 92%
“…Observational work indicates that radio AGN, at least in the local Universe, are more common in early-type galaxies (ETGs). For example, Kaviraj et al (2015) have shown that the detection rate in very long baseline interferometry (VLBI) observations for ETGs is around an order of magnitude higher than in their late-type counterparts, when galaxy stellar mass is controlled for -this is qualitatively similar to the findings of other studies in the literature (e.g. Ledlow et al 2001;Sadler et al 2014).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also note that AGN activity has been found to peak during different stages along the merger quenching sequence (Schawinski et al 2010;Koss et al 2010;Ellison et al 2011;Carpineti et al 2012;Kaviraj et al 2015;Carpineti et al 2015). As we discussed above the definition of the post merger and blue early type stage depends on the specifics of the sample and the method used to select, for instance, post merger galaxies.…”
Section: Red Early Type Stagementioning
confidence: 83%
“…power and the SFR. In addition irregular fuel supply (Tadhunter et al 2011;Kaviraj et al 2015) and variability in the AGN "on" phase (Hickox et al 2014) will further weaken the correlation.…”
Section: Radio Power and Sfr Relationmentioning
confidence: 99%